The relationship between attachment and anxiety. Comparative study between teenagers with disabilities coming from paternal versus maternal single-parent families - Tudor, Marinela; Sandu, Mihaela Luminița; Rus, Mihaela (Eximia, 2024)
Starting from the hypothesis that the formation of a different type of attachment than the secure one can generate anxiety - a disturbing phenomenon of social adaptation, manifested by excessive fear - the present study aimed to investigate this aspect in the context of adolescents with multiple disabilities. This thematic choice constituted the motivational foundation of the research. The main purpose of the study was to examine, within the selected sample, if there are significant differences in the development of disabled adolescents, depending on their origin from a single-parent family environment, either maternal or paternal. More specifically, the research looked at the relationship between anxiety level and attachment style in adolescents with multiple disabilities in the sample. The study sample was set at 50 subjects, aged between 15 and 18 years. After analyzing the data and establishing a standard, a non-random sampling method with quotas was chosen. The criteria for inclusion in the population were: female and male adolescents, aged between 15 and 18 years, coming from single-parent or nuclear (two-parent) families, the presence of multiple disabilities, with the exception of severe intellectual disability or other conditions that could limit the understanding of the questionnaire items, balancing the number of female and male participants, as well as those from single-parent and two-parent families. The research methodology included the use of interviews and questionnaires. To identify the attachment style, the Attachment Style Questionnaire (C.S.A.), developed by Collins and Read in 1990, was used. To measure the level of anxiety, two anxiety questionnaires were combined, adapting their wording to be accessible to participants with impairments associated with mild or moderate intellectual disability. Therefore, the main objective of this study was to examine the relationship between attachment style and anxiety among adolescents with multiple disabilities, with a particular focus on identifying significant differences between these variables.